On the Influence of Message/Audience Specifics and Message Appeal Type on Message Empowerment: The Austrian Case of COVID-19 Health Risk Messages. Issue 13 (10th November 2022) - Koinig, Isabell
ABSTRACT: A pandemic is a unique form of health crisis that requires intensive communicative efforts. In order to achieve positive health outcomes, messages need to be carefully designed. In this context, both message specifics and audience specifics receive consideration. This research tries to scrutinize (1) which message appeal (emotional vs. informative) is perceived more favorable by the Austrian public, (2) which message appeal (emotional vs. informative) leads to a higher degree of message empowerment, and (3) the degree to which message empowerment can be enhanced by (a) message specifics and (b) a combination of message and audience specifics. A quantitative survey with 337 Austrians revealed that the emotional appeal message led to a higher degree of message empowerment than the informative appeal message. Moreover, only message specifics were found to enhance message empowerment. Implications for message design are derived, before limitations and directions for future research are addressed.